Leishmaniose cutânea no estado do Ceará : aspectos históricos, clínicos e evolução terapêutica - Sousa, Anastácio de Queiroz (2009)
Cutaneous leishmaniasis is an important health problem in Brazil.The disease has spread to all regions and autochtonous cases have been reported from all states. The total number of cases reported in the country from 1980 to 2005, was 613, 644. In Ceará, cutaneous leishmaniasis is an endemic disease in all regions of the state and in many municipalities hundreds of cases are reported every year. In times of epidemics the number of cases has reached more than 4000 per year. In the 28 years from 1980 to 2008, 55.925 new cases were reported in the state. The first well documented cases of cutaneous leishmaniasis in Ceará date back to 1925. Even though it causes a great impact in public health, many informations related to the knowledge of the disease are lacking in its historical, clinical and therapeutics aspect. Objective:1.To study all relevant historical aspects related to the leishmaniasis;2. To investigate when and how it emerged in Ceará, as well as who studied it; 3. To describe in a detailed form the clinical manifestations of cutaneous leishmaniasis; 4. To describe the historical evolution of therapy as well as to propose a therapeutic alternative for the disease. Methods:We consulted primary and secondary sources. Secondary sources. 1. Old books (classics) on leishmaniais; Books and articles from the beginning of the XX century by writers from Ceará as well as thesis and articles from scientific journals. 2. Archives of Libraries in Fortaleza(Ce), Salvador(BA), Rio de Janeiro(RJ), São Paulo (SP), EUA( Universidade de Virginia, Universidade de Miami) and England (London School of Tropical Medicine & Hygiene and Wellcome Foundation); 3. Search in pubmed, Medline and lilacs; 4. To search information from microfilms of newspapers and reports from the Government Province of Ceará from 1850 to 1930 in the archives of Menezes Pimentel Public Library in Fortaleza (Ce); 5. WHO home page, yahoo.com and google.com, specially for scientists biographies. Primary sources: 1. Interview with researchers, family members of old researchers that made the history. 2. Author personal archives of photographs of cutaneous leishmaniasis patients skin and mucosal lesions as well as lymph nodes. Results: The first references to the existence of the disease (in books) in Ceará are form 1909 and in government reports are from 1917. The emergence of the disease in Ceará occurred after the great drought and the smallpox epidemic (1877-1879). These phenomenons forced migration of dozens thousands of people to the Amazon, to work on rubber production. In their return they brought with them the infection and the disease found here the appropriate conditions to develop. The first documented information on the disease in the Amazon region date back to 1820. From the clinical point of view, we documented that the infection by Leishmania braziliensis causes fever, malaise and satellite lymph nodes enlargement and in some patients liver and spleen enlargement is seen. Lymph nodes aspirates demonstrated Leishmania in most patients and Leishmania was cultured from Buffy coat of one patient. Concerning therapy, 21 patients were treated with fluconazole 7mg/kg/day for an average of 7 weeks, 18 were cured, and 2 of the three that did not responded to fluconazole initially, were cured with drugs associations that included fluconazole in the therapeutic scheme. Conclusion: 1. Cutaneous leishmaniasis in Ceará is an imported disease from the Amazon region, where the condition exists since the beginning of the XIX century and had its arrival in Ceará at the end of the XIX century; 2. Leishmania braziliensis infection causes a systemic disease due to parasite dissemination and it is probable in this phase, that leishmania locates in the mucosa, where it may causes disease in a later phase; 3. Fluconazole is a therapeutic alternative for cutaneous leishmaniasis.